2010
DOI: 10.1111/j.1365-2036.2010.04331.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors of bleeding related to post‐banding ulcer following endoscopic variceal ligation in cirrhotic patients: a case‐control study

Abstract: SUMMARY BackgroundLife-threatening bleeding caused by early spontaneous slippage of rubber bands has been described after variceal ligation in cirrhotic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
123
4
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(138 citation statements)
references
References 28 publications
8
123
4
3
Order By: Relevance
“…In a study of 605 patients undergoing variceal ligation, 21 (3.5%) patients had spontaneous bleeding due to band slippages confirmed at endoscopy, and 11 died. 198 Rebleeding due to band-induced ulcers has been found to occur in up to 14% of patients. [199][200][201][202] Multivariate analysis in the first study found no increased risk of bleeding in those on aspirin, although this applied to only 8/605 patients.…”
Section: Oesophageal Variceal Bandingmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of 605 patients undergoing variceal ligation, 21 (3.5%) patients had spontaneous bleeding due to band slippages confirmed at endoscopy, and 11 died. 198 Rebleeding due to band-induced ulcers has been found to occur in up to 14% of patients. [199][200][201][202] Multivariate analysis in the first study found no increased risk of bleeding in those on aspirin, although this applied to only 8/605 patients.…”
Section: Oesophageal Variceal Bandingmentioning
confidence: 99%
“…[199][200][201][202] Multivariate analysis in the first study found no increased risk of bleeding in those on aspirin, although this applied to only 8/605 patients. 198 There have been no studies of the risks of haemorrhage following variceal banding in patients on thienopyridenes, ticagrelor or DOAC, and indeed it would be usual to discontinue these drugs, if possible, in a population at such a high risk of haemorrhage.…”
Section: Oesophageal Variceal Bandingmentioning
confidence: 99%
“…[7,18,20] In addition, prior variceal digestive bleeding, high platelet ratio index (APRI score), peptic esophagitis and low prothrombin index are also deemed bleeding risk factors after early spontaneous slippage of the EVL rubber band. [19] However, it remains controversial whether coagulation status predicts bleeding after EVL.…”
Section: Risk Factorsmentioning
confidence: 99%
“…[17,18] Although uncommon, the mortality rate is up to 52%, mainly due to infectious complications. [19] Our group is conducting a controlled prospective trial aiming to analyze outcomes after treatment of osteoporosis or osteopenia in cirrhotic patients (119 subjects) with esophageal varices. Until now only 17 patients required 26 EVL sessions (Child-Pugh classes A, B and C were 6, 10 and 1, respectively).…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation